Foreword - Epure, Manuela (Annals of Spiru Haret University. Economic Series, 2016)
Looking closely on today’s economic and social environment one can easily identify some significant drivers such as: population ageing and long active workforce, globalization effects on emerging markets, transparency as necessary approach of any policy making process. Population ageing is one of the greatest trends shaping the 21st century social, economic and political life.